Mechanism of the wintertime Aleutian Low-Icelandic Low seesaw - Sun, Jie; Tan, Benkui (Geophysical Research Letters, 2013)
The driving mechanism for the wintertime (December-March) Aleutian Low-Icelandic Low (AL-IL) seesaw is investigated with National Centers for Environmental Prediction/National Center for Atmospheric Research reanalysis data for 1948-2009. It is shown that the AL and the IL are dynamically linked through the eastern Pacific wave train (EPW) and that both the EPWs and the stratospheric polar vortex are found to work cooperatively to produce a significant AL-IL seesaw. In general, it is found that wave reflection by the polar vortex is crucial for the formation of the AL-IL seesaw. However, when the EPWs are extremely strong, the AL-IL seesaw appears to be caused primarily by horizontal wave propagation. It is further shown that the Pacific center of the traditional Arctic Oscillation pattern is present when the AL-IL seesaw is active, but it disappears when the AL-IL seesaw is absent. Geosciences, Multidisciplinary SCI(E) EI 1 ARTICLE 15 4103-4108 40